Deblurring by Solving a TVp-Regularized Optimization Problem Using Split Bregman Method. (16th December 2014) - Xiao, Su
Abstract : Image deblurring is formulated as an unconstrained minimization problem, and its penalty function is the sum of the error term and TV p -regularizers with 0 < p < 1 . Although TV p -regularizer is a powerful tool that can significantly promote the sparseness of image gradients, it is neither convex nor smooth, thus making the presented optimization problem more difficult to deal with. To solve this minimization problem efficiently, such problem is first reformulated as an equivalent constrained minimization problem by introducing new variables and new constraints. Thereafter, the split Bregman method, as a solver, splits the new constrained minimization problem into subproblems. For each subproblem, the corresponding efficient method is applied to ensure the existence of closed-form solutions. In simulated experiments, the proposed algorithm and some state-of-the-art algorithms are applied to restore three types of blurred-noisy images. The restored results show that the proposed algorithm is valid for image deblurring and is found to outperform other algorithms in experiments.